1999
DOI: 10.1161/01.cir.100.13.1400
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilation to Bradykinin Is Mediated by an Ouabain-Sensitive Pathway as a Compensatory Mechanism for Impaired Nitric Oxide Availability in Essential Hypertensive Patients

Abstract: Background —In essential hypertension, endothelium-dependent vasodilation is impaired because of reduced nitric oxide (NO) availability, which is mainly caused by oxidative stress. The present study was designed to identify the mechanism(s) responsible for NO-independent vasodilation to bradykinin in patients with essential hypertension. Methods and Results —In 16 healthy subjects (49.5±5.8 years; 118.6±3.5/78.9±2.9 mm Hg) and 16 patients with essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
94
1
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 32 publications
13
94
1
1
Order By: Relevance
“…In agreement with previous observations, 13,35 the response to bradykinin but not to sodium nitroprusside was found to be reduced in patients with essential hypertension as compared with normotensive control subjects. Moreover, whereas L-NMMA inhibited the vasodilating response to bradykinin in normotensive subjects, it was ineffective in patients with essential hypertension.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous observations, 13,35 the response to bradykinin but not to sodium nitroprusside was found to be reduced in patients with essential hypertension as compared with normotensive control subjects. Moreover, whereas L-NMMA inhibited the vasodilating response to bradykinin in normotensive subjects, it was ineffective in patients with essential hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…12 In the presence of impaired NO availability, endothelium-dependent relaxation seems to be sustained by hyperpolarization, which probably acts as a compensatory mechanism. 13 Since endothelial dysfunction and oxidative stress are promoters of atherosclerosis 14 -16 and are closely related to cardiovascular events, [17][18][19] it is conceivable that an adjunctive target for antihypertensive treatment, in addition to blood pressure lowering, could be represented by restoration of could be represented by prevention of oxidative stress and restoration of NO availability. 20 Although several antihypertensive drugs can increase endothelium-dependent vasodilation in patients with essential hypertension, few results are available concerning the mechanism underlying this effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rossoni et al (43) found that nanomolar concentrations of ouabain induce the release of an endothelium-derived relaxing factor that seems to open K Ca channels. In addition, increased EDHF production has been described in different hypertension models, probably to compensate for the vascular tone increase (30,50). The K Ca channel blocker TEA potentiated the response to phenylephrine more strongly in segments of aorta from ouabain-treated than untreated rats.…”
Section: Discussionmentioning
confidence: 99%
“…De plus, ces réponses sont également altérées chez l'animal dans divers modèles d'hypertension, de diabète, d'athérosclérose ou de choc septique [37,[40][41][42][43][44]. À l'inverse, les réponses attribuées à l'EDHF peuvent exercer un rôle compensateur quand la voie de la NO-synthase est altérée chez les patients hypertendus [45] ou dans des modèles animaux de dénudation et de régénération endothéliale [46]. L'amélioration des réponses attribuées à l'EDHF peut contribuer à la restauration de la fonction endothéliale lors de différentes interventions thérapeutiques.…”
Section: Les Réponses Attribuées à L'edhf: éPiphénomène Ou Rôle Physiunclassified